Penentuan Zona Permeabel Berdasarkan Analisis Kerapatan Kelurusan Citra DEM-SRTM Dan 3D Micromine Software pada Potensi Panas Bumi Daerah Gunung Papandayan, Jawa Barat - Ratih C F Ratumanan; Ari Wakanno (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to identify permeable zones influencing geothermal manifestations in Mount Papandayan, West Java, which holds geothermal potential. The area's geology conditions indicate that geothermal manifestations are closely related to geological structures, interpreted from ridge and valley alignments in DEM SRTM imagery. These structures form weak zones serving as pathways for geothermal fluids to reach the surface. The analysis involves interpreting lineaments from DEM SRTM data to calculate lineament density, visualized using roset diagrams and 3D models in Micromine. Results show dominant lineament orientations trending Northeast–Southwest, Northwest–Southeast, and West–East. Field validation confirms geothermal features such as fumaroles, hot springs, and altered rocks in faulted zones, marked by fault scarps and sharp river bends. Lineament density in the study area varies, categorized as low (6.1–11.6 km⁻¹), medium (11.7–16.9 km⁻¹), and high (17.0–24.0 km⁻¹). Geothermal manifestations tend to appear in high-density zones associated with fractures or faults, which function as recharge and discharge channels for geothermal fluids. The 3D model supports the link between fault presence and geothermal surface manifestations in the area.